Investiční rozhodování v IT a ROI jako prostředek měření přínosů ITSM pro business - Zakharenkava, Sviatlana; Voříšek, Jiří, 1950-; Tolar, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2008)
The Diploma Thesis is dealing with questions of investment decision-making in the area of IT and can be a complete guidance on the basic concepts of decision-making on the investment projects, methods of financial evaluation of such projects and the ways of its application in the sphere of IT. It is mainly aimed on the projects dealing with internal processes in IT organizations and optimalization of its management ? IT Service Management (ITSM). The paper deals with existing methodologies and standards applicable to IT Service Management and closely works with the latest library of best practices ITIL V3. The introduction gets the reader into the basics of the IT management, introduces the existent market standards and creates a liaison between the IT and business in questions of investments. The second part pays attention to the principles of ITSM and describes the benefits that can process optimalization bring to the company. The third chapter opens up the IT investment topic and introduces various methodological concepts and models used not only in the classical financial theory, but in the modern management practice as well. It offers a basic overview on the methods of investment project evaluation, e.g. Net Present Value (NPV), The Payback Period Method, The Internal Rate of Return (IRR), The Profitability Index, and the most popular one ? Return on Investment (ROI). The following chapter applies the measure of Return on Investment (ROI) to the projects of ITSM implementation according to ITIL. It shows the basic principles of the method usage, describes its main components and introduces the way of identification and evaluation of the benefits, which those projects bring to the business. Gained knowledge is based on the real practical examples ? several worked-out business cases created for the customers of the Hewlett-Packard Company.
The last part of this chapter shortly describes several software tools for building the similar business cases and their own methodology. The last chapter in devoted to the situation on the local and world market and addresses the practical application of the methods of IT projects evaluation in the companies. The conclusion then summarizes important parts and key elements of the paper.
Vedoucí práce: Jiří Voříšek
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2008
Rok obhajoby 2008
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses